Healthcare facility water, sanitation, and hygiene service status and barriers in Addis Ababa, Ethiopia - Atimen Derso; Taffere Addis; Bezatu Mengistie (Journal of Water, Sanitation and Hygiene for Development, 2023)
Inadequate water, sanitation, and hygiene (WASH) practices within healthcare facilities heighten the likelihood of hospital-acquired infections. Therefore, this study aimed to assess the status of WASH services and barriers at public healthcare facilities in Addis Ababa. A converging parallel mixed design was conducted among 86 public health care facilities and 16 key informants. A stratified sampling technique was used to select health care facilities. Quantitative data was collected using a semi-structured checklist, and qualitative data was collected using key informant interviews. Thematic data analysis was done to identify the barriers. Independent analysis of the healthcare WASH domain revealed that 86% and 14% of healthcare facilities had access to basic and limited water services, respectively; 100% had limited access to sanitation services; and 88.4% had limited hand hygiene services. While 97.7% and 29% did not have environmental cleaning or waste management services, respectively. Lack of WASH service infrastructure, resource availability, governance and collaborative work, capacity and awareness building, and a framework for monitoring and evaluation were found to be barriers to WASH services. Lack of basic WASH service access and existing challenges at healthcare facilities hinder efforts towards infection prevention and control. HIGHLIGHTS 100% of healthcare facilities had limited access to sanitation service.; 88.4%, and 3.5% of healthcare facilities had limited, and no service access for hand hygiene, respectively.; 97.7% and 29% of healthcare facilities had not environmental cleaning service and waste management service respectively.; Lack of access to basic WASH services, combined with multiple existing challenges at healthcare facilities in Addis Ababa, hinders efforts towards pandemic and healthcare-acquired infection prevention and control.;